Assessing Thermal Comfort and its Impact on Student Satisfaction in Selected Hostels at Caleb University, Imota, Lagos State - Opeyemi A. ASAJU; Cephas ADELORE; Akintunde O. ONAMADE; Jonathan B. ADEWUMI; Glory A. ODUBANJO; Gbenga O. WILLIAMS; Enoch O. OYELEYE (FUDMA Journal of Engineering and Technology, 2025)
Whether residential, commercial, educational, or industrial buildings, the level of comfort derived within space is a function of how conductive it is. Environmental factors are a key determinant that cannot be overlooked as a major player to satisfaction. Parameters like indoor air quality, acoustic comfort, thermal comfort and visual comforts are usually considered under it. A satisfying space relaxes and rejuvenates the occupant making them productive within or outside depending on the type. To this end, the study assessed the impact of thermal comfort on students’ satisfaction in selected hostels at Caleb University, Imota, Lagos State. 727 students responded to the structured questionnaire survey that was administered through google form comprising of both open and closed-ended questions. The responses were analyzed using SPSS and result presented. The finding reveals that thermal discomfort in student accommodations frequently resulting from inadequate temperature control impairs sleep quality and adversely affects academic performance and overall well-being. The placement of windows is crucial in determining thermal comfort, demonstrating the most significant correlation with students’ overall life satisfaction. The study concluded that a large proportion of students report health effects because of uncomfortable temperatures. This could include respiratory problems, headaches, and other illnesses exacerbated by poor heat control. To increase students’ comfort and contentment in hostels, the main recommendation is to focus on lowering heat-related discomfort, as this has the largest impact on overall satisfaction. Hostel designs should focus on thoughtful window placement to boost thermal comfort, which in turn can enhance students’ sleep quality, academic success, and overall health.